Relationship Between Treatment Compliance Level and Vision Value in Post-Phacomulsification Cataract Surgery Patients at Rumah Sakit Bhayangkara Lumajang - Yuliawardani, Prahesty; Abidin, Zainal; Kusyairi, Achmad (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Cataracts are one of the causes of blindness, successful cataract treatment does not depend on surgery alone. Postoperative care and treatment greatly influences visual outcomes after surgery. The research aims to explain the relationship between the level of treatment compliance and visual acuity in patients after phacomulsification cataract surgery at Rumah Sakit Bhayangkara Lumajang. The research design used was analytical observational with a cross sectional approach. The target population is 70 patients with cataracts who check up at the eye clinic, the target population is post-cataract surgery patients who are controlled at the eye clinic with a amount of 46 patients. The research sample consisted of 45 respondents who were selected using the Accidental Sampling technique. Data collection used the MMAS-8 questionnaire to measure the level of treatment compliance and the Snellen Chart to measure visual acuity values. Data analysis used the Spearman rank correlation test. The results of measuring the level of compliance with treatment of patients after phacomulsification cataract surgery at Rumah Sakit Bhayangkara Lumajang were obtained by 17 patients (37.8%) of the amount respondents who had a low level of treatment compliance. The results of measuring the vision values of 16 patients (35.6%) of the amount respondents had good vision values. The results of data analysis using the Spearman rank correlation test showed a significant relationship between the level of treatment compliance and vision scores with a value of ρ = 0.000 < 0.05. This shows that the more compliant the treatment is, the better the visual acuity score. Research shows that patient compliance with post-cataract surgery treatment is critical for optimal recovery. High compliance is associated with improved vision, so disciplined patients tend to have better vision. These findings emphasize that interventions to improve patient compliance should be a top priority in cataract treatment, and postoperative patient compliance needs to be considered